Interpretation of The Process of Artificial Intelligence-based Human Creation: Between Chat GPT and Meta AI - Hakim, Mohamad Fikri; Nurrohim, Ahmad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
This research examines the relationship between Qur'anic verses describing the process of human creation and modern scientific knowledge through a linguistic and scientific analysis approach supported by Artificial Intelligence (AI). The focus lies on verses from Surah Al-Mu'minun, Al-Insan, and As-Sajdah, which describe the stages of human creation, starting from nutfah (sperm), alaqah (a clinging embryo), to mudghah (a lump of flesh). Spiritual elements such as the soul are also discussed to highlight the transcendent dimension that science cannot fully explain. This study employs a qualitative method, using AI as a primary source for data exploration and analysis through specific prompts or questions. Thematic analysis is applied to categorize the information obtained from AI into main themes corresponding to the stages of human creation mentioned in the Qur'an. The research reveals a profound alignment between Qur'anic terminology and modern embryology. For instance, nutfah in embryology refers to the germ plasma, while nutfatun amshaj corresponds to fertilization. The term alaqah aligns with the embryo stage, and mudghah corresponds to gastrulation. Furthermore, izham relates to osteogenesis or ossification, and lahm corresponds to myogenesis. The concepts of ruh and tannur are associated with the womb, while takhliq represents formation and development, encompassing processes such as fertilization, mitosis, and cell differentiation. Additionally, taqdir aligns with determination, encompassing genetics, epigenetics, and hormonal factors, and amal signifies the formation and development of body structures.This research highlights the harmony between the Qur'anic descriptions of human creation and the findings of modern embryology, providing a deeper understanding of the Qur'an's scientific and spiritual insights.